2013
DOI: 10.1177/1077546313481050
|View full text |Cite
|
Sign up to set email alerts
|

Performance of N-Z systems in the mitigation of underground blast induced vibration of structures

Abstract: Control of structural vibration due to wind and earthquake forces has been extensively researched. However, studies on vibration control of structures against underground blasts are limited. It is thereby important to study the usefulness of established vibration control technologies in the blast resistant design of structures. In the present work, an attempt is made to study the effectiveness of the New-Zealand (N-Z) type base isolator (BI) in mitigating structural vibration effects due to blast induced groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…e performance of baseisolated buildings under blast-induced ground motion (BIGM) has also captured attention in the recent times. Mondal et al [27,28] have studied the response of buildings isolated by lead-rubber bearing (N-Z system) under BIGM. Further, the performance of a base isolation system equipped with shape-memory alloy in protecting buildings under BIGM has been studied by Mondal et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…e performance of baseisolated buildings under blast-induced ground motion (BIGM) has also captured attention in the recent times. Mondal et al [27,28] have studied the response of buildings isolated by lead-rubber bearing (N-Z system) under BIGM. Further, the performance of a base isolation system equipped with shape-memory alloy in protecting buildings under BIGM has been studied by Mondal et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the blast effects considered in case 1, i.e., R1, resulted in the most catastrophic destructions to the structure, considering the blast charge of 50 tons and a 100 m standoff distance. Blast wave R1 is primarily considered in the present study due to the accidental blast loading, as reported by Mondal et al [57]. Thus, by implementing appropriate retrofitting measures, such as shear walls, the story drift can be effectively controlled, ensuring the buildings' structural stability, and minimizing the potential for damage and failure during blast events.…”
Section: Resultsmentioning
confidence: 87%
“…Wu et al proposed mitigation of ground shock effects on structures by the provision of a sand layer in the foundation of the structure. The suitability of rubber in the foundation layer for vibration control of structures under BIGM was also reported by Ranasinghe et al Motivated by these studies, the effectiveness of the lead‐plug or New‐Zealand (N‐Z) BI system for structural protection against underground BIGM was studied by the authors and the occurrence of large bearing displacement and its residual deformation for high blast intensity were noted. This was also observed under near‐field earthquake motions that often contain a long‐period pulse in the velocity–time history as reported by Hall et al and Mazza and Vulcano and under such cases performance of the conventional bearings is not very reliable .…”
Section: Introductionmentioning
confidence: 74%
“…It has been noted in the previous study, that the normalized yield strength of the N‐Z isolator ( F 0 ) plays an important role in the isolation efficiency as well as affects significantly the peak and residual displacements of the bearings. As the normalized forward transformation strength of SMA ( F S 0 ) is analogous to F 0 , F S 0 will influence the efficiency of the SMARB isolation system.…”
Section: Numerical Studymentioning
confidence: 99%